Hubungan Tingkat Pengetahuan dan Tingkat Konsumsi Energi, Protein dengan Status Gizi Siswa SMP Negeri 3 Jorong Kabupaten Tanah Laut - Fitria Aningsih; Wahyu Hardi Prasetyo; Diah Setiawati; STIKES Husada Borneo; BLUD RS Ulin Banjarmasin; Alumni STIKES Husada Borneo (HB PRESS, 2013)
One of the basic asset is human resources and productive potential. Nutrition is one of the major determinants of the quality of human resources (HR). The vision is to realize the nutritional self-aware to realize optimal nutrition Healthy Indonesia 2010. The purpose of this study is to know a relationship among the level of knowledge, level of energy consumption, protein and students’ nutritional status of junior haigh shcool 3 Jorong Districk Tanah Laut. Research methods, analytic with cross sectional study, the population in this study were all students aged 12-16 totaled 107 in junior haigh shcool 3 Jorong Districk Tanah Laut by the number of samples 57 people. Analysis conducted descriptive and statistical chi-square test. The results obtain There was correlation between knowledge and nutritional status with p = 0.044, There was correlation between energy consumption and nutritional status with p = 0.003, and there is correlation between the level of protein intake and nutritional status of students in junior high scool 3 Jorong District Tanah Laut with p = 0.008. It’s expected to increase knowledge about proper nutrition and apply it in everyday life, so as to have a good nutritional status.